Dampak Psikologis Kekerasan Rumah Tangga Dan Mekanisme Pemulihan Korban - Sapril Sapril; Mersi Aprilia; Ria Anggraeni Utami (CV. ITTC INDONESIA, 2026)
This study examines the psychological impact of domestic violence and victim recovery mechanisms with the aim of identifying key issues, assessing the effectiveness of support services, and providing recommendations for improvement. Using a mixed approach, including a survey of 150 urban victims and in-depth interviews with 20 service providers and survivors, the study analyzed trauma symptoms, coping strategies, and access to legal, medical, and psychosocial support. Results indicate a high prevalence of anxiety, depression, and post-traumatic stress symptoms, limited access to integrated services, and barriers resulting from social stigma and weak inter-agency coordination. Recommendations include strengthening multisectoral referral networks, expanding trauma-based counseling services, and implementing community-based public awareness programs to enhance victim recovery.